Effect of Defoliation at Different Stages on Grain Sorghum Yield and Yield Components - Kraig L. Roozeboom (Kansas Agricultural Experiment Station Research Reports, 2024)
Loss of leaf area usually results in yield loss in grain crops, but the amount of yield loss varies with extent and timing of defoliation. Grass crops, such as corn and grain sorghum, are particularly sensitive to leaf area loss near the time of seed set because there is little opportunity for the plant to compensate. An experiment to quantify yield reductions associated with various levels of defoliation imposed at different stages of grain sorghum development was conducted at Manhattan, KS, in 2023. Target defoliations of 0, 33, 66, and 100% were imposed at 5-leaf, flag leaf appearance, half bloom, and hard dough stages. Defoliation of 5-leaf sorghum resulted in minimal yield loss unless the defoliation rate was 100%, which delayed heading, increased heads per plant, and reduced head size. Leaf area losses approaching 100% at the hard dough stage caused minimal yield reductions in a year with high temperatures and minimal rainfall during grain fill. Yield reductions were greatest when leaf area was lost at flag leaf appearance or half bloom. Leaf area loss of 60% or greater caused yield losses of 40% to 70%. These yield losses were associated with different combinations of reductions in head size and seed size depending on timing of leaf loss.
Keywords: grain sorghum; defoliation; yield; yield components; developmental stages